The Climate Siren: Hanna Cormick's The Mermaid. Issue 3 (September 2022) - Stevens, Lara; Varney, Denise
Abstract : An accomplished dancer, acrobat, and physical theatre performer, Hanna Cormick became ill in 2014 with a trifecta of rare genetic conditions that make her severely allergic to pollutants in the air — smoke, detergents, and food particles — and her bones and internal organs prone to dislocation. In January 2020, during Australia's summer of unprecedented bushfires, Cormick staged The Mermaid, risking her life to make a performance about the climate emergency and how we are all vulnerable bodies at risk in a changing environment.